2016
DOI: 10.1007/s00213-015-4199-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propranolol on conversational reciprocity in autism spectrum disorder: a pilot, double-blind, single-dose psychopharmacological challenge study

Abstract: Acute propranolol administration improved conversational reciprocity in ASD. Further exploration of these preliminary findings, as well as other potential treatment response predictors, with serial doses is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 51 publications
2
35
1
Order By: Relevance
“…Both were open trials without controls, and both demonstrated remission of tantrums, property destruction, and self-injurious behavior in one-half the patient samples after 6 weeks of treatment with the non-selective beta blockers propranolol or nadolol (17). These trials revealed subtler improvements in speech and social behavior in all eight subjects (18), consistent with controlled trials demonstrating improvement of word fluency (19) and conversational reciprocity (20) with propranolol in ASD. In comparison, the response of the above patient in the present case report during the first week of treatment was faster than that of the patients in these studies and at a lower dose of propranolol (40 mg per day versus at least 100 mg per day).…”
Section: Therapeutic Use Of Beta Blockers In Asdsupporting
confidence: 54%
“…Both were open trials without controls, and both demonstrated remission of tantrums, property destruction, and self-injurious behavior in one-half the patient samples after 6 weeks of treatment with the non-selective beta blockers propranolol or nadolol (17). These trials revealed subtler improvements in speech and social behavior in all eight subjects (18), consistent with controlled trials demonstrating improvement of word fluency (19) and conversational reciprocity (20) with propranolol in ASD. In comparison, the response of the above patient in the present case report during the first week of treatment was faster than that of the patients in these studies and at a lower dose of propranolol (40 mg per day versus at least 100 mg per day).…”
Section: Therapeutic Use Of Beta Blockers In Asdsupporting
confidence: 54%
“…Potential discrepancies in observable behaviors that may be reported by parents versus internal feelings that can be reported by the child might contribute to differences in findings. In studies of individuals with ASD, however, use of self‐report can be challenging given that some individuals with ASD may have difficulty reporting on internal feelings and emotions [e.g., Losh & Capps, ; Zamzow et al, ]. Moreover, much of previous research has been conducted in adolescents clinicially diagnosed with an internalizing disorder [e.g., Dahl et al, ], while the current study did not compare those with or without a clinical diagnosis of anxiety or depression.…”
Section: Discussionmentioning
confidence: 90%
“…A few studies in high‐functioning adolescents and young adults with ASD have investigated the correlations of the eye tracking with standardized assessments of clinical dimensions. Some of these have found an association between the total fixation times in looking at the mouth and stronger language and social skills in various measures of socialization, ADOS [Klin et al, ], VABS [McPartland, Webb, Keehn, & Dawson, ; Norbury et al, ], Social Responsiveness Scale [Fujioka et al, ], and Autism Diagnostic Interview‐Revised (ADI‐R) [Zamzow et al, ]. Moreover, correlations between fixation on faces and the overall severity of autism as assessed by the Childhood Autism Rating Scale and the ADI‐R [Grynszpan & Nadel, ] have also been described.…”
Section: Discussionmentioning
confidence: 99%